Factors affecting the implementation of green building development projects among housing developers in the Klang Valley, Malaysia (IR) - Ainul Samihah Albahori (2018)
This research aims to study the factors affecting the implementation of the green building development project among housing developers in Malaysia. The objectives of this study are to identify how far the housing development in Malaysia has implemented the green building principles; to evaluate the factors affecting the implementation of the green building development, and to suggest a guideline to encourage the implementation of the green building development among housing developers in Malaysia. The methods used for this study are a combination of case study, quantitative and qualitative. A total of 234 housing developers returned a complete questionnaire. The results of the quantitative analysis were brought to two interview sessions in case study to verify the findings. This research found that there are five green building principles that are frequently being implemented by housing developers which are ‘encouraging green design and innovation’, ‘water efficiency’, ‘energy efficiency’, ‘consumption of green materials and resources’, and ‘application of the green building certification’. The findings show that the external factors in the form of social and cultural factors affect green building\ implementation among housing developers. Therefore, to encourage the green building implementation, a guideline was suggested to tackle the social and cultural factors. The internal factors of attitude and value, as well as the external factor, namely the economic factor was also considered in the proposed guideline to facilitate the implementation of green building development. This research contributes to the body of knowledge by providing a useful basis for researchers to study factors affecting the implementation of green building among housing developers.